Two new species and a new subspecies of Tetraclitella (Cirripedia: Thoracica) from the Cainozoic of Australia and New Zealand and a consideration of the significance of tubiferous walls - Buckeridge, John S. (Zootaxa, 2008)
A tubiferous cirripede Tetraclitella judiciae sp. nov., previously known only from two isolated and incomplete shell wall plates identified as Tetraclitella sp. cf. T. purpurascens (Wood, 1815), is described from the early Miocene of Victoria, Australia; a further taxon, Tetraclitella purpurascens miocenica subsp. nov., occurs in the late Miocene-Pliocene of Victoria, and specimens from the early Miocene of New Zealand, previously recorded as Tetraclitella sp. cf. T. purpurascens (Wood, 1815) are redesignated as Tetraclitella nodicostata sp. nov. Tetraclitella is the first cirripede genus known to have had tubiferous walls. Incorporation of chitinous stringers within the shell wall of early tetraclitids (e.g. Epopella) may have facilitated the development of the tubiferous shell wall, which permitted sessile barnacles to maximise the shell strength to calcite ratio: in doing so, these chitinous stringers not only reduced the diversion of energy required to extract calcium carbonate from seawater, but improved the effectiveness of the shell wall in resisting predators. It is also argued here that the presence of chitin within the shell increased resistance to both corrasion and corrosion, the latter becoming an increasing problem for calcareous shelled organisms following a drop in the pH of seawater after the PalaeoceneEocene Thermal Maximum.